A new species of Xenorhipis LeConte and of Mastogenius Solier from Mexico, with a discussion of Chrysobothris ichthyomorpha Thomson and its allies and notes on other Mexican and Central American Buprestidae (Coleoptera) - Westcott, Richard L. (Zootaxa, 2008)
Xenorhipis bajacalifornica Westcott, new species, from Baja California Sur, Mexico, is described and figured. A description of Mastogenius cyanelytron Westcott, new species, herein is necessitated by the fact M. cyanelytra Westcott is an unavailable name. Three species in a complex Neotropical group of the genus Chrysobothris, C. chiriquita Obenberger, new status, C. ichthyomorpha Thomson, and C. thomsoni Waterhouse are discussed in detail and figured. A lectotype is designated for C. chiriquita. Buprestis transversepicta Kerremans is reported as known only from Mexico and is figured. Notes are provided for an additional 135 species in the genera Acmaeodera, Acmaeoderopsis, Actenodes, Agrilaxia, Agrilus, Buprestis, Chalcophora, Chrysesthes, Chrysobothris, Colobogaster, Euchroma, Eudiana, Euplectalecia, Hiperantha, Hippomelas, Jelinekia, Knowltonia, Lampetis, Mixochlorus, Paragrilus, Pelecopselaphus, Polycesta, Spectralia, Tetragonoschema, and Thrincopyge.